Whole‐exome sequencing of oral mucosal melanoma reveals mutational profile and therapeutic targets. Issue 3 (5th February 2018) - Lyu, Jiong; Song, Zhijian; Chen, Jianhua; Shepard, Matthew J; Song, Hao; Ren, Guoxin; Li, Zhiqiang; Guo, Wei; Zhuang, Zhengping; Shi, Yongyong
Abstract: Oral mucosal melanoma (OMM) is a rare and aggressive subtype of melanoma with little known about its pathogenesis or carcinogenesis. We therefore performed whole‐exome sequencing (WES) on 19 matched OMM tumor/normal pairs in order to gain insight into potential genetic drivers of tumor formation. For the first time, we describe the comprehensive mutational profile of OMM. Our data suggest that the genetic background of OMM differs from those of other melanoma subtypes. We identified recurrent mutations involving KIT, POLE, PTPRD, PTCHD2, and DMXL2 . Notably, copy number analysis revealed recurrently amplified regions of 12q14 (57.9%, containing CDK4 ) and 5p15 (47.4%, containing TERT ). CNV analysis in a separate cohort of 15 samples validated the frequent CNV in CDK4 and TERT . We also observed that the melanocyte development and pigmentation signaling pathway is frequently altered in OMM. Furthermore, our data suggest several altered genes that may be amenable for targeted therapy. We identified one patient with metastatic OMM in our cohort who was identified to harbor a targetable KIT mutation using our WES results. This patient was able to achieve complete remission following implementation of KIT ‐targeted therapy. These findings provide further insight into the genetic underpinnings of OMM development and suggest that patients with OMM may benefit from WES analysis to identify potential targetable genetic mutations. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.